Pengukuran Tingkat Kebergunaan Aplikasi PLN Mobile Menggunakan Model System Usability Scale dan Teori Jakob Nielsen - Pratama, Regi; Sudrajat, Antonius Wahyu (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2023)
The PLN Mobile application is an application developed by PLN, the purpose of this application being developed is to make it easier for PLN customers to reach services at PLN. However, the difference between PLN customers and current PLN Mobile Application users is very large, thus allowing research to measure how much the PLN Mobile Application is useful. Measurements were made using the System Usability Scale (SUS) model and Jakob Nielsen Theory. The SUS model is a usability measurement model of an application using 10 questionnaire questions given to respondents, the data is processed using the sus model calculation and produces an average usability score, these results can determine the value of the application, user acceptance of the application, as well as the usability ranking category for application based on SUS interpretation scale. To find out what needs to be fixed in the application, the authors add 5 variables in Jakob Nielsen's theory. This study used 400 respondents with the scope of the PLN Mobile Application users who were in the Toboali area only. Based on the processed data, the average SUS score is 71.11, with this result it can be seen that the level of acceptance of the application user is acceptable to the user, the PLN Mobile application is in the good category. by obtaining a value of C+ . and on the results of Jakob Nielsen's theory, the overall average score range is 4.35 which is in the Very Good category, the lowest result is the Errors variable, which is 3.14, thus improvements to the application can be focused on aspects of errors that exist in the application PLN Mobile. Keywords: PLN Mobile Application, System Usability Scale model, Usability.